2017
DOI: 10.1016/j.cjtee.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and interleukin-10 plasma levels and mRNA expression in polytrauma patients

Abstract: PurposeHost response to polytrauma occasionally has unpredictable outcomes. Immune response is a major factor influencing patient's outcome. This study evaluated the interaction of two main cytokines in immune response after major trauma, specifically interleukin-6 (IL-6) and interleukin-10 (IL-10). Plasma level of these cytokines is determined by mRNA expression of these cytokines genes which may decide the outcome of polytrauma patients.MethodsThis prospective multicenter trial held at four trauma centers en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 14 publications
3
37
0
1
Order By: Relevance
“…Meduri and colleagues showed that high levels of IL1B and IL6 in plasma from ARDS patients predict a poor outcome in ARDS patients [20]. The role of inflammatory mediators in course of PT is described in many publications [4,8,20,21,34,35]. The intravenous administration of MSC may ameliorate the dysregulation of the immune system, reduce apoptosis, improve regenerative processes and prevent complications after PT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meduri and colleagues showed that high levels of IL1B and IL6 in plasma from ARDS patients predict a poor outcome in ARDS patients [20]. The role of inflammatory mediators in course of PT is described in many publications [4,8,20,21,34,35]. The intravenous administration of MSC may ameliorate the dysregulation of the immune system, reduce apoptosis, improve regenerative processes and prevent complications after PT.…”
Section: Discussionmentioning
confidence: 99%
“…PT patients revealed increased serum level of IL6, IL10, CXCL1 and CCL2 at the admission to hospital (0 h). The study of Sapan and colleagues included 54 PT patients and investigated the dysregulation of the immune system of PT patients by determining the ratio IL6/IL10 in plasma by ELISA and messenger RNA expression [35]. Disproportional amounts of IL6 and IL10 are a predictor for the development of multiple organ dysfunction syndrome and death [35].…”
Section: Discussionmentioning
confidence: 99%
“…3 Furthermore, In trauma patients, a strong correlation between the mRNA and plasma levels of other inflammatory cytokines such as interleukin IL-6 and IL-10 has been shown. 45 The mRNA and protein plasma concentrations of IL-21 in SAP are elevated compared to those in MAP patients (Figure 1 and 3). Although the mRNA and protein plasma levels showed increased IL-21 in SAP compared to MAP, these were however not significant except in on day 9 (mRNA).…”
Section: Discussionmentioning
confidence: 88%
“…IL-10 is an anti-inflammatory cytokine that regulates and limits acute inflammation in response to trauma to prevent tissue damage, such as secondary brain damage after TBI [ 21 , 45 ]. IL-10 plays a crucial role in inflammatory and autoimmune diseases of the intestine, chronic infections, tumor development, neuroinflammation, -degeneration as well as multiple organ dysfunction syndrome (MODS) and MOF after polytrauma, where IL-10 levels from 21.0 to 340.7 pg/mL were shown [ 42 , 46 ]. In this study, the highest IL-10 levels were measured on admission and a continuous decrease until day 5 was shown.…”
Section: Discussionmentioning
confidence: 99%